WANPRESTASI VERSUS PERBUATAN MELANGGAR HUKUM MENURUT BURGERLIJK WETBOEK - NURTI WIDAYATI; IAN NURPATRIA SURYAWAN (Media Bisnis, 2016)
Every engagement comes from the agreement and the law. According to article 1243 of the Civil Code any reimbursement of expenses, losses, and interest on the non-fulfillment of an engagement, then shall be obligated, if the debtor, having been declared inattentive to his engagement, remained negligent, or if something to be given or made, within the time limit that has been passed. According to article 1365 of the Civil Code that any act of unlawful conduct, which carries harm to another party, shall be for that person who is guilty of damages. There is a clear distinction between default and unlawful acts.